(untitled) (Orfeu, 2019)
With the gathering of data, premiere dates, interviews, first performances, recordings and critiques, as well as more than 30 unpublished articles in newspapers and periodicals, this article has two purposes: first, to make a genealogy of the three versions devised by Villa-Lobos for one of his still little known vocal pieces, the Song of an Eighteenth Century Poet; then, to assess whether the debate around aesthetic and/or stylistic issues was already present in the early records, performances and musical critiques that the work received throughout the 1960s and 1970s. The results raise a possible look at Villa-Lobos’s production for voice and guitar from the concept of “transitive identity” proposed by Llanos (2018).